Synoptic climatology associated with extreme snowfall events in Sapporo city of northern Japan. (25th March 2014) - Farukh, M. A.; Yamada, Tomohito J.
Abstract Synoptic‐scale atmospheric circulations are crucial for extreme snowfall events. On the basis of topmost 100 snowfall intensity days in Sapporo, Hokkaido, Japan over winter seasons from 1992 to 2011, this study uses principal component analysis and K‐means clustering to characterize synoptic circulation patterns. Composite maps were constructed for sea‐level pressure, 850 hPa moisture and wind field, and 500 hPa geopotential height. The circulation patterns of the topmost seven snowfall events were triggered by the advection of very cold airmass from eastern Siberia, anomalously huge moisture with northerly strong wind, active and stationary Aleutian low, and 500 hPa deep cold‐core low over the southern Hokkaido.